EVALUASI KINERJA MAHASISWA SEKOLAH TINGGI PARIWISATA NUSA DUA BALI DALAM MELAKSANAKAN PROGRAM PRAKTIK KERJA NYATA - I Gusti Ayu Putu Wita Indrayani (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2017)
This study aims to determine the performance of students of Bali Tourism Institute in implementing a real working practice program (a.k.a PKN), especially for the students of Hospitality Department. In-depth interview techniques were conducted on five key informants at five credible hotels in Bali. The results showed that the performance of STPNB students during implementing PKN program in the industry is considered good enough. There are five dimensions used to measure student performance such as work quality, quantity of work, timeliness, work efficiency, and independence. Of the five dimensions, it can be seen that the dimension of quality of work and independence received a very positive assessment of the informants. In addition, the authority factor is the most dominant factor in influencing performance compared to other factors such as effectiveness and efficiency, discipline, and initiative. Based on the key informants, there are several important efforts to improve the work competence of Bali Tourism Institute students in industry, such as adjustment for curriculum, textbook, and teaching materials; Implementation of learning collaborative learning model, and implementation of periodic training / training activities.